2022
DOI: 10.3389/fpsyg.2022.941466
|View full text |Cite
|
Sign up to set email alerts
|

Changes in authoritarianism before and during the COVID-19 pandemic: Comparisons of latent means across East and West Germany, gender, age, and education

Abstract: Modern theories of authoritarianism have stressed the importance of threat to the expression of authoritarian attitudes and intolerance. Arguably, authoritarian tendencies may have increased during COVID-19 pandemic, a major threat to life and security. One issue arising when comparing mean scores is that of measurement invariance. Meaningful comparisons are only possible, if latent constructs are similar between groups and/or across time. This prerequisite is rarely ever tested in research on authoritarianism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These results contrast with research conducted in Poland (Golec de Zavala et al., 2021) and the United Kingdom (Fischer et al., 2023), showing that, although SDO remained stable, authoritarianism increased after the outbreak of COVID‐19. Other research conducted with a German sample reveals that authoritarianism was also lower in 2020 compared to 2017 (Heller et al., 2022). Of course, the cultural contexts differ markedly between New Zealand and Germany but one possibility for their shared trends in RWA is that both nations had more progressive leaders—Prime Minister Jacinda Ardern and Chancellor Angela Merkel, respectively—who were praised for their clear communication styles and who heavily weighted scientific recommendations in their COVID‐19 policy decisions (The Lancet Infectious Diseases, 2020).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These results contrast with research conducted in Poland (Golec de Zavala et al., 2021) and the United Kingdom (Fischer et al., 2023), showing that, although SDO remained stable, authoritarianism increased after the outbreak of COVID‐19. Other research conducted with a German sample reveals that authoritarianism was also lower in 2020 compared to 2017 (Heller et al., 2022). Of course, the cultural contexts differ markedly between New Zealand and Germany but one possibility for their shared trends in RWA is that both nations had more progressive leaders—Prime Minister Jacinda Ardern and Chancellor Angela Merkel, respectively—who were praised for their clear communication styles and who heavily weighted scientific recommendations in their COVID‐19 policy decisions (The Lancet Infectious Diseases, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…The uniform restrictions on the entire nation may have also increased perceptions of social conformity, thereby reducing threats to social cohesion and decreasing RWA. Indeed, although RWA increased at the pandemic's onset in the United Kingdom (Fisher et al., 2023), Germany saw a reduction in authoritarianism the first year of the pandemic compared to 2017 (Heller et al., 2022). Thus, context may play an important role in how ideological beliefs change during a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…While recent studies have argued that both claims have validity (Arikan, 2023;Stevens & Banducci, 2022), the COVID-19 pandemic added an additional wrinkle to the debate. This shock event, seemingly with implications for security that are likely to elicit a response among authoritarians, did not increase their support for more authoritarian measures to address the threat (e.g., Heller et al, 2022;Hibbing, 2022;Vowles, 2022). Although at first glance, this may seem to confirm the revisionist theory-indeed, it was libertarians who were more supportive of such measures-neither did the response to COVID-19 appear to reflect the permanent state of alert among authoritarians claimed by Hetherington and Weiler (2009); rather, authoritarians appeared to diminish the threat of COVID-19.…”
mentioning
confidence: 91%
“…Consider that experimentally induced COVID threats among White Americans have increased discrimination towards Asians (see Lu et al., 2021; Zhao et al., 2022), whereas a British study (Meleady & Hodson, 2022) tracking naturally occurring changes in COVID‐perceptions over time found that decreases in COVID‐threat coincided with reduced outgroup avoidance (and no changes in anti‐immigrant attitudes). Consider also that, during COVID‐19, RWA (characterized by conventionality, submission to authorities, and punitiveness towards outgroups) decreased in Germany (Heller et al., 2022) but increased in the United States (Pazhoohi & Kingstone, 2021), whereas other American research found little association between political ideology and objective COVID‐related changes (e.g., cases; restrictions) (Stern & Axt, 2022). In a large‐scale comparison of 11 countries, most countries exhibited no relation between ideology and COVID‐reactions except for American respondents, for whom increases in right‐ (vs. left‐) leaning ideologies were associated with greater ignoring of social distancing recommendations (Becher et al., 2021).…”
Section: Introductionmentioning
confidence: 99%